Factors contributing to bone mineral density among Chinese women in the Klang Valley, Malaysia - Lau, Lee Ting (2016)
Osteoporosis and its related fractures have become epidemic health problem over the years. However, the studies on bone mineral density (BMD) and its related factors were limited in Malaysia. The purpose of this study was to determine the bone health status and examine the contribution of sociodemographic background, family history of fracture, reproductive history, biochemical measures, dietary intake, lifestyle practices as well as anthropometric measurements towards BMDs among healthy Chinese women residing in the Klang Valley. Subjects were participants from a 12- month milk supplementation study conducted from 2012 to 2014. There were 263 women, of which 137 were premenopausal and 126 were postmenopausal women. A pre-tested questionnaire and three validated questionnaires, namely International Physical Activity Questionnaire (IPAQ), Weekly Sun Exposure Questionnaire and Food Frequency Questionnaire (FFQ), were administered through interview to collect details of all variables, except biochemical measures which were collected through fasting blood and urine samples. Dual-energy X-ray absorptiometry (DXA) scan examined BMD at total body, L1-L4 spine and total hip. All variables that were significant at bivariate analysis were selected into respective models of BMDs in stepwise multiple linear regression (MLR). The mean age of the subjects was 50.0 ± 10.3 years. Prevalence of osteoporosis was 1% and 4% at total body and lumbar spine BMD in postmenopausal subjects. There were 1% of premenopausal subjects who had L1-L4 spine and total hip BMD below the expected range for age. Postmenopausal subjects presented significant lower mean BMD at all sites (p<0.05). Older age, lower education level and lower monthly household income as well as higher parity, bone turnover rate [Procollagen Type 1 NTerminal Propeptide (P1NP), osteocalcin (OC) and C-telopeptide of type I collagen crosslinks (CTX)], energy and nutrients intake, physical activity measure, body mass index (BMI), fat mass, measures of central obesity were observed among postmenopausal women (p<0.05). Vitamin D deficiency (<50 nmol/L) was presented in 42.5%, of which 2/3 was contributed by premenopausal subjects. Mean serum 25-hydroxyvitamin D, physical activity measure, habitual and current calcium intake were reported as 56 ± 20 nmol/L, 1040 MET-minutes/week, 499 ± 202 mg/day and 330 mg/day, respectively. Among the variables, menopausal status had shown to develop the strongest correlation with BMDs, especially at L1-L4 spine BMD (r= -0.570, p<0.01). Age and biochemical measures, particularly urinary CTX also demonstrated moderate and negative association with BMDs (p<0.01). Besides, weight and lean mass presented higher magnitude than BMI and fat mass, respectively, in positive relation with BMDs. Despite weaker associations, lower BMDs were associated with lower education level, presence of family history of fractures, multiparous, higher physical activity measure, smoking and higher central obesity measures. Stepwise multiple linear regression analyses on three skeletal sites showed 40.1%, 42.1% and 17.2% variances in the regulation of BMD at total body, L1-L4 spine and total hip, respectively. Significant contributors of BMDs were as following: urinary CTX towards all BMD sites; menopausal status and lean mass towards total body and L1-L4 spine BMD; weight towards total hip BMD. In conclusion, this study presented the bone heath status and identified risk of low bone mass significantly contributed by high CTX, being postmenopausal, low anthropometric measurements of lean mass and weight among Chinese women throughout middle-aged and senior adulthood. Where low physical activity level, low dietary calcium intake and vitamin D deficiency were prevalent, appropriate health promotion programs should be carefully planned to optimize bone health status among Chinese women in Malaysia.